Peran Metode Investigasi Kelompok dalam Meningkatkan Hasil Belajar PAI Siswa Kelas X di SMK Walisongo 2 Depok - Aji, Muhammad; Nurul Milla, Sri; Fadil, Khaidir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The background of the problem in this study is the relatively low learning outcomes of Islamic Religious Education for class X students of SMK Walisongo 2 Depok, which is shown from the learning outcomes of students who are still under the minimum completeness criteria (KKM). The aims of this study were (1) to determine the increase in student learning outcomes class X SMK Walisongo 2 Depok on PAI subjects which are taught using the lecture method (2) To find out the increase in student learning outcomes of class X SMK Walisongo 2 Depok on PAI subjects which are taught using the Group Investigation method. (3) To find out whether there is a significant difference in improving the learning outcomes of class X students of SMK Walisongo 2 Depok in PAI subjects between classes taught using the Lecture Method and classes taught using the Group Investigation Method. This study used a quasi-experimental approach with a control group pretest-posttest design. The participants in this study were 66 students of SMK Walisongo 2 Depok, class X, with class X AKL as the experimental class for learning with the Group Investigation Method and class X OTKP 2 as the control class. The results showed that: (1) the level of student learning outcomes in the control class There was an increase in PAI learning outcomes of 25.6 (55.17%). (2) class student learning outcomes. increase in Islamic education learning outcomes for class X students at Walisongo 2 Vocational School Depok between classes taught using the lecture method and classes taught using the Group Investigation method. So it can be concluded that the group investigation method has a fairly effective role in improving the learning outcomes of class X PAI at SMK Walisongo 2 Depok.